Mannitol Polymorphs as Carrier in DPIs Formulations: Isolation Characterization and Performance - Ayça Altay Benetti; Annalisa Bianchera; Francesca Buttini; Laura Bertocchi; Ruggero Bettini (MDPI AG, 2021)
The search for best performing carriers for dry powder inhalers is getting a great deal of interest to overcome the limitations posed by lactose. The aerosolization of adhesive mixtures between a carrier and a micronized drug is strongly influenced by the carrier solid-state properties. This work aimed at crystallizing kinetically stable D-mannitol polymorphs and at investigating their aerosolization performance when used in adhesive mixtures with two model drugs (salbutamol sulphate, SS, and budesonide, BUD) using a median and median/high resistance inhaler. A further goal was to assess in vitro the cytocompatibility of the produced polymer-doped mannitol polymorphs toward two lung epithelial cell lines. Kinetically stable (up to 12 months under accelerate conditions) α, and δ mannitol forms were crystallized in the presence of 2% w/w PVA and 1% w/w PVP respectively. These solid phases were compared with the β form and lactose as references. The solid-state properties of crystallized mannitol significantly affected aerosolization behavior, with the δ form affording the worst fine particle fraction with both the hydrophilic (9.3 and 6.5%) and the lipophilic (19.6 and 32%) model drugs, while α and β forms behaved in the same manner (11-13% for SS; 53-58% for BUD) and better than lactose (8 and 13% for SS; 26 and 39% for BUD). Recrystallized mannitol, but also PVA and PVP, proved to be safe excipients toward lung cell lines. We concluded that, also for mannitol, the physicochemical properties stemming from different crystal structures represent a tool for modulating carrier-drug interaction and, in turn, aerosolization performance.